Analisis Perbaikan Kondisi Lingkungan Kerja Terhadap Beban Kerja Mental - Sri Rahayuningsih (Department Industrial Engineering, University of Muhammadiyah Malang, 2014)
Good condition of environmental work will support workers in performing operations maximally. Factors e.g. temperature, noise, and vibration have contribution in increasing psychological distress and affect to worker’s performance. PR Rezeki Abadi is a cigarette manufacturer which utilizes manual power of workers for establishing production in the whole flow process, starting from mixing materials (tobacco, sauce, and clove) until finishing. In accordance with measurement results, temperature and noise of environmental condition in mixing process workplace is higher than normal level so operators in this workplace get high psychological distress and often do mistakes in terms of mixing process. This research aims to develop environmental work condition particularly in the mixing material workplace and measure mental workload by using SWAT in order to find out the influence of environmental work development. Based on the development of environmental work condition through additional blower and use of earplug, it is obtained that temperature and noise intensity emerge in proper level with normal condition at 25–27°C and 75dB. The result of workload measurement using SWAT method shows that workload in average is under 40 so in other words the workload after development can be categorized as low level.